Conic Trust Region Method for Linearly Constrained Optimization (Journal of Computational Mathematics, 2003)
In this paper we present a trust region method of conic model for linearly constrained optimization problems. We discuss trust region approaches with conic model subproblems. Some equivalent variation properties and optimality conditions are given. A trust region algorithm based on conic model is constructed. Global convergence of the method is established.